Analog Design for CMOS VLSI Systems - Maloberti, Franco. (The International Series in Engineering and Computer Science, 2001)
Analog Design for CMOS VLSI Systems is a comprehensive text that offers a detailed study of the background principles and the analog design techniques for CMOS-VLSI implementation. The book covers the physical operation and the modelling of MOS transistors. Discusses the key features of integrated passive components and studies basic building blocks and voltage and current references before considering in great details the design of op-amps and comparators. The book is primarily intended for use as a graduate-level textbook and for practising engineers. It is expected that the reader should be familiar with the concepts taught in basic introductory courses in analog circuits. Relying on that proper background knowledge the book presents the material on an intuitive basis with a minimum use of mathematical quantitative analysis. Therefore, the insight induced by the book will favour that kind of knowledge gathering required for the design of high-performance analog circuits. The book favours this important process with a number of inserts providing hints or advises on key features of the topic studied. An interesting peculiarity of the book is the use of numbers. The equations describing the circuit operation are guidelines for the designer. It is important to assess performances in a quantitative way. To achieve this target the book provides a number of examples on computer simulations using Spice. Moreover, in order to acquire the feeling of the technological progress, three different hypothetical technologies are addressed and used. Detailed examples and the many problems make Analog Design for CMOS VLSI Systems a comprehensive textbook for a graduate-level course on analog circuit design. Moreover, the book will efficiently serve the practical needs of a wide range of circuit design and system design engineers.